Reducing operative morbidity among female patients combining laparoscopic hysterectomy and laparoscopic ventral hernia mesh repair procedures: a single centre 14 years experiences - Agrawal, Priti; Agrawal, Rishi Kumar; Chandrakar, Jyotirmay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: During laparoscopic ventral hernia repair (LVHR) mesh is used and so this procedure is not combined with any other major surgery, due to the risk of mesh infection. We did laparoscopic hysterectomy (LH) with LVHR in our study group and found it to be safe procedure with excellent patient recovery and satisfaction rates. Aims and objectives of the study was to assess the short- and long-term clinical outcomes of doing LH and LVHR simultaneously. The primary objectives were to evaluate the intraoperative and post-operative complications, mesh infection rates, hernia recurrence rates and patient satisfaction rates for at least 4 years. Methods: This prospective study was conducted at Aarogya Hospital and test tube centre from 1st January 2007 to 31st December 2016 and follow up completed by 31st December 2020. Total 100 women were included, willing for LH and LVHR simultaneously irrespective of the size of uterus and hernia defect size up to 7cms. Results: Maximum number of patients 65% were in the age group of 45-55 years. 70% patients had previous surgeries commonest being LSCS in 46% cases. Hernia defect size was between 3-5 cm in length and width in 70% cases, requiring dual mesh fixation in 68% cases of size 15x15cms. Our recurrence rate for hernia was nil, 98% cases were highly satisfied with the surgical outcomes by the end of 4 years follow-up. Conclusions: We emphasize that LH can be easily done with LVHR in combination reducing operative morbidity.